SYNTHESIS AND BIOMATERIAL CHARACTERIZATION OF ZINC NANOPARTICLE FROM SEA GRASS OF CYMODOCEA SERRULATA AND THEIR ANTIOXIDANT POTENTIAL - Venkateshwaran V, Dr. Abirami Arthanari, Dr.Sivaperumal, (Chelonian Research Foundation, 2023)
Introduction The present study investigates the green synthesis of zinc nanoparticles using sea grass (Cymodocea serrulata) extract as both a reducing and stabilizing agent. The synthesized nanoparticles were thoroughly characterized for their biomaterial properties, including size, morphology, crystal structure, stability, and surface chemistry. Furthermore, their antioxidant potential was evaluated through standard antioxidant assays. Materials and methods Results These findings suggest that sea grass-derived zinc nanoparticles possess attractive biomaterial characteristics and remarkable antioxidant potential, positioning them as promising candidates for diverse applications in fields ranging from biomedicine to environmental science. The green synthesis approach employed in this study underscores their eco-friendly and sustainable nature. Future research should delve into specific applications, biocompatibility assessments, and potential mechanisms underlying their antioxidant activity. Conclusion This study contributes to the expanding knowledge of green synthesis methods for nanoparticles and underscores the potential of sea grass-derived zinc nanoparticles as multifunctional biomaterials with significant antioxidant properties. Keywords: Cymodocea serrulata, Antioxidants activity, Zinc , Nanoparticle, Green synthesis, Plant extract.